EXPLORING TEACHER PERCEPTION ON THE MERDEKA BELAJAR CURRICULUM IN TAPOS DISTRICT ELEMENTARY SCHOOLS - Ajisoko, Pangkuh; Misbahudin; Ai Jamilah; Lulu Nazwa Diaz; Siti Nofiyah (JURNAL PENDIDIKAN GLASSER, 2025)
This study explores teachers' perceptions of the Merdeka Belajar (Independent Learning) curriculum and the challenges they face in its implementation. Using a quantitative approach, data were collected through a questionnaire survey administered to elementary school teachers in the Tapos District, Depok, West Java. The results indicate that 24% of teachers found the curriculum good, while 76% rated it very good. These findings suggest that the majority of teachers have successfully implemented the curriculum, which emphasizes character education based on the Pancasila Student Profile. Despite positive feedback, some challenges remain, such as limited facilities, insufficient teacher training, and technological barriers. This study highlights the need for targeted teacher support and infrastructure improvements to optimize curriculum implementation.